1997
DOI: 10.1111/j.1539-6924.1997.tb00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Cultural Differences in Risk Perception: A Model‐Based Approach

Abstract: The present study assessed cross-cultural differences in the perception of financial risks. Students at large universities in Hong Kong, Taiwan, the Netherlands, and the U.S., as well as a group of Taiwanese security analysts rated the riskiness of a set of monetary lotteries. Risk judgments differed with nationality, but not with occupation (students vs. security analysts) and were modeled by the Conjoint Expected Risk (CER) model?') Consistent with cultural differences in country uncertainty avoidance,(2) CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(142 citation statements)
references
References 29 publications
7
134
1
Order By: Relevance
“…The results are consistent with the findings of the previous literature (e.g. Bontempo et al 1997;Seddighi et al 2001;Fuchs and Reichel 2004;Pizam et al 2004;Mavondo 2006a, 2006b). While Asian tourists perceive a greater influence of tornadoes on international travel than other nationality groups, the US tourists perceive this influence to be relatively low.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results are consistent with the findings of the previous literature (e.g. Bontempo et al 1997;Seddighi et al 2001;Fuchs and Reichel 2004;Pizam et al 2004;Mavondo 2006a, 2006b). While Asian tourists perceive a greater influence of tornadoes on international travel than other nationality groups, the US tourists perceive this influence to be relatively low.…”
Section: Discussionsupporting
confidence: 93%
“…For example, significant differences in travel risk perception were found across various national cultures (Seddighi et al 2001;Fuchs and Reichel 2004;Pizam et al 2004;Movondo 2006a, 2006b). It was found that the risk perception of the Chinese significantly differs from that of Westerners (Bontempo et al 1997). Tourists from low Uncertainty Avoidance (UAI) cultures tend to perceive lower risks than tourists from high UAI cultures (Hofstede and Hofstede 2005).…”
Section: Differences In the Perceptions Of Natural Disasters And Travmentioning
confidence: 99%
“…The two items are not, therefore, correlates. Bontempo, Bottom and Weber (1997) have, alternatively, associated uncertainty avoidance with risk aversion, but Hofstede explicitly states that uncertainty avoidance is not the same as risk avoidance (Hofstede, 1981(Hofstede, | 2001. For these reasons, correlations between UAI and the measures employed in the study were not assumed.…”
Section: Discussionmentioning
confidence: 99%
“…Weber et al (1998) conclude that Chinese proverbs endorse more risk taking than American proverbs, reflecting risk taking differences between these cultures. Bontempo et al (1997) determine that Asians (Hong Kong and Taiwan) perceive greater risk than American and Dutch respondents to lotteries having a small probability of large losses. If this translates to food safety perceptions, Asians might perceive greater food safety risk for a food safety hazard that has very small prevalence but potentially serious health consequences than would Americans.…”
Section: Previous Literaturementioning
confidence: 97%